Gender Dysphoria and A De-Transition to the Biological Gender: A Case Report from a Primary Care Perspective - Fathima Begum SM; Hizlinda T; Sharifah Najwa Syed Mohamad; Khadijah Hasanah AA; Hatta S; Mohd Radzniwan A Rashid (UKM, 2024)
Indexed by WOS/MyCite